2014
DOI: 10.1177/0004563214545117
|View full text |Cite
|
Sign up to set email alerts
|

Serum and synovial fluid chemokine ligand 2/monocyte chemoattractant protein 1 concentrations correlates with symptomatic severity in patients with knee osteoarthritis

Abstract: Objective: Serum and synovial fluid (SF) chemokine ligand 2 (CCL2)/monocyte chemoattractant protein 1 (MCP-1) concentrations have been identified to be increased in osteoarthritis (OA) patients. The scope of this study was to examine CCL2 concentrations in serum and SF of knee OA patients and to explore their association with patientreported symptomatic severity. Method: One hundred and sixty-one knee OA patients and 138 healthy controls were enrolled into the study from our hospital. We collected Western Onta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 27 publications
3
53
1
2
Order By: Relevance
“…At later stages, also other CCR2 ligands (CCL2, CCL8, CCL7 and CCL13) are detectable in articular cartilage. These findings are consistent with human studies that noted increased human CCL2 and CCR2 in patients with OA(35, 36). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At later stages, also other CCR2 ligands (CCL2, CCL8, CCL7 and CCL13) are detectable in articular cartilage. These findings are consistent with human studies that noted increased human CCL2 and CCR2 in patients with OA(35, 36). …”
Section: Discussionsupporting
confidence: 92%
“…Consistent with studies suggesting a role as a mediator of OA pain (14,15, 36), we were also able to demonstrate that CCR2 signaling inhibition reduced pain by examining joint loading as a measure of pain response.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, it was reported that levels of CCL2, a major monocyte chemoattractant in serum and synovial fluid obtained from individuals with OA correlated positively with pain and physical disability 15. Further, microarray analyses of genes expressed in knees of mice with surgery-induced OA showed that Ccl2 is upregulated as early as 6 hours and 7 days after surgery when there is no apparent histological changes) relative to sham-operated controls (see online supplementary figure S1A).…”
Section: Resultsmentioning
confidence: 96%
“…Additional studies have reported that synovium from individuals with joint injuries such as meniscal tears, a major risk factor for OA development, have elevated chemokine expression suggesting that these chemokines might instigate inflammatory responses in such individuals 13 14. Furthermore, a recent study reported that synovial fluid levels of CCL2 (or MCP-1) correlated positively with pain and physical disability in patients with OA 15. In line with this, it has been shown that deficiency in CCR2, the main receptor for CCL2, reduces OA-related pain mouse OA 16.…”
Section: Introductionmentioning
confidence: 99%
“…Specially, CCL3 is elevated in pre-X-ray-defined patients and CCL3 has a high ability to discriminate pre-X-ray patients from healthy people, suggesting CCL3 is a potential diagnostic marker for early detection of the disease [86]. Recently, it was reported that CCL2 concentrations in SF are positively correlated with pain score as defined by WOMAC, suggesting that CCL2 is a marker for symptomatic severity of OA [97]. …”
Section: Inflammatory Markersmentioning
confidence: 99%